Stress hormones are associated with inflammatory cytokines and attenuation of T-cell function in the ascites from patients with high grade serous ovarian cancer - Alexandra N. Aquino-Acevedo; Hope Knochenhauer; Yesenia Castillo-Ocampo; Melanie Ortiz-León; Yadiel A. Rivera-López; Camily Morales-López; Melanie E. Cruz-Robles; Elvin R. Hernández-Cordero; Shonagh Russell; Regina Whitaker; Margarita Bonilla-Claudio; Dung-Tsa Chen; et al. (Brain, Behavior, & Immunity - Health, 2022)
Mounting evidence suggests that chronic stress and subsequent distress can promote ovarian cancer progression. These altered psychological states have been linked to sustained release of stress hormones, activation of the β-adrenergic receptors in ovarian cancer cells, and induction of pro-tumoral signaling pathways. In addition, data suggest that chronic stress promotes an inflammatory landscape highlighted by increased infiltration of tumor-associated macrophages into the ovarian tumor microenvironment (TME). In ovarian cancer, ascites is a unique TME comprised of tumor, and immune cells, which secrete pro-tumoral cytokines and chemokines that modulate tumor-associated immunity. However, our knowledge about how stress hormones impact the ascites TME remains limited. We hypothesized that the ascites harbors measurable levels of stress hormones, and accumulation of these in the ascites generates a pro-tumorigenic, inflammatory, and immunosuppressive TME. We evaluated ascites samples from 49 patients with high grade serous ovarian cancer (HGSOC) and quantified cortisol and stress hormones metabolites, metanephrine (MN), and normetanephrine (NMN) in all samples. We also measured 38 individual cytokines in the ascites, including several pro-inflammatory cytokines, such as IL-6, which were positively correlated to MN or NMN levels of those samples. Conversely, we found cortisol levels were negatively correlated to several pro-inflammatory cytokines. As T-cells are integral to the TME and our analyses identified cytokines in the ascites known to modulate T-cell function, we characterized ascites-derived T-cells and assessed the impact of stress hormones on the T-cell phenotype. Our data show an altered CD4+/CD8+ T-cell ratio and a heterogeneous expression of exhaustion markers in T-cells from the ascites, while ascites-derived CD8+ T-cells exposed to epinephrine had decreased co-expression CD38 and Granzyme B. To extend these findings to animal models, we subjected ovarian cancer-bearing mice to daily restraint stress, which resulted in increased tumor growth in two models. Congruent with our human analyses, we detected corticosterone, MN, and NMN in the ascites from tumor-bearing mice, and these stress hormones correlated with several inflammatory cytokines. Moreover, daily restraint stress leads to increased CD4+PD-1+/CD8+PD-1+ T-cell ratio in the ovarian tumor microenvironment. Overall, these data highlight a role of stress hormones in the ascites TME as a driver of tumor-associated inflammation, T-cell suppression, and disease progression.